Role and Importance of Family at Preschool Children Environmental Education - Güven, Seval; Yılmaz, Nihan (European Journal of Sustainable Development, 2017)
Environmental problems we face recently are not a surprise. These problems are a result of years of unconsciousness. Changing negative, insensitive, unconscious human behaviours; obtaining wanted behaviours and showing empathy toward the environment are possible with just environmental education. If Environmental Education and Consciousness are not taught to the all community and necessary precautions are not taken, environmental problems in twenty first century which we are in will become more and more serious problem. Giving first education in family is very important because this education will become the base of person’s life. Parents are the first teachers oftheir children. They are foremost responsible for their children’s growth and education until they start school. Parents responsibilities and powers over their children’s education could be utilized and extended during preschool education by the help or planned educational activities that require active involvement of parents. This education will help solving the environmental problems we experience and bringing up new generations who live within nature. Keywords: environmental education, family and environment, pre-school period.